Evaluation of the Efficacy and Safety of Thalamotomy and Pallidotomy Using Focused Ultrasound (FUS) in the Treatment of Essential Tremor and Parkinson’s Disease: A Literature Review - Kuna, Paweł Jan; Gołdyn, Mateusz; Turczynowski, Konrad; Turczynowski, Kamil; Pietrucha, Jakub; Lichoń, Jakub; Kuna, Wojciech; Chojniak, Alicja; Haberko , Wiktoria (Quality in Sport, 2026)
Introduction: Parkinson’s Disease (PD) and Essential Tremor (ET) are the two most prevalent movement disorders, with tremor being a core, often drug-refractory, motor feature. While traditional surgical treatments like Deep Brain Stimulation (DBS) and Radiofrequency (RF) ablation are effective, they are invasive and carry inherent risks such as hemorrhage and infection, necessitating craniotomy. This reality drives the need for less invasive therapeutic options for patients with advanced, medication-refractory symptoms and motor fluctuations. Aim: The aim of this systematic review is to assess the clinical efficacy and safety profile of Thalamotomy and Pallidotomy performed using Magnetic Resonance-Guided Focused Ultrasound (MRgFUS) technology in the treatment of Essential Tremor and Parkinson’s Disease. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was conducted using keywords: Focused Ultrasound (FUS), Essential Tremor (ET), Parkinson’s Disease (PD), Thalamotomy, Pallidotomy, MRgFUS. Conclusion: MRgFUS-guided thalamotomy (VIM) and pallidotomy (GPi) constitute a breakthrough, non-invasive alternative to traditional surgical ablations. The technology demonstrates high and durable efficacy, achieving a 47% reduction in ET tremor and a 39,1% reduction in PD motor symptoms (UPDRS III), comparable to invasive standards. Crucially, MRgFUS offers a favorable safety profile by eliminating the risk of surgical bleeding and infection while providing real-time lesion monitoring. However, a key limitation remains the requirement for an adequate Skull Density Ratio (SDR), excluding some clinically eligible patients. Further long-term, prospective studies are required to fully establish its role.